Mortality and complications in Omani patients with beta-thalassemia major: a long-term follow-up study - Daar, Shahina; Al-Naamani , Khalid; de Sanctis, Vincenzo; Al Rahbi, Sarah; Al Zadjali, Shoaib; Khan, Hammad; Panjwani, Vinodh; Al-Khabori, Murtadha (Acta Biomedica Atenei Parmensis, 2023)
Background and aim:Beta thalassemia major (β-TM) is a genetic blood disorder requiring lifelong blood transfusions.  The resulting iron overload damages multiple organs, particularly the heart and endocrine organs. This study aimed to describe and assess the predictors of survival and complications in Omani patients with β-TM. Methods: All β-TM patients registered in the day care of Sultan Qaboos University Hospital were included in this retrospective study. Results: There were 187 patients with β-TM with a median follow-up of 24.9 years.  The median ages at diagnosis and the start of chelation were 0.7 and 4.8 years, respectively. The following complications developed at different time points [Median (age in years), Complication Free Probability at 20 years]: Death (20.0 years;85%), hypogonadism (15.9 years;50%), insulin-dependent or non-insulin dependent diabetes (20.0 years;88%), cardiac complications (20.3 years;91%), osteoporosis (20.7 years;96%), hypothyroidism (25.7 years;97%), liver complications (7.3 years;54%). The number of complications predicted death (P = 0.0038). Those born after 1980 had a lower risk of death (P = 0.005), hypogonadism (P = < 0.0001), and cardiac complications (P = 0.004). Higher serum ferritin at the start of chelation was associated with the development of diabetes (P = < 0. 001). Conclusions: This long-term study shows complications development at different ages, and the number of complications is associated with survival. Later birth cohorts had a lower risk of death, hypogonadism, and cardiac complications. There was a persistent negative impact of delay in the start of iron chelation that is present even after a long follow-up. (www.actabiomedica.it).